2010
DOI: 10.1371/journal.pone.0015870
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Driven AMPA Receptor Redistribution Mimicked by Selective Dopamine Neuron Stimulation

Abstract: BackgroundAddictive drugs have in common that they cause surges in dopamine (DA) concentration in the mesolimbic reward system and elicit synaptic plasticity in DA neurons of the ventral tegmental area (VTA). Cocaine for example drives insertion of GluA2-lacking AMPA receptors (AMPARs) at glutamatergic synapes in DA neurons. However it remains elusive which molecular target of cocaine drives such AMPAR redistribution and whether other addictive drugs (morphine and nicotine) cause similar changes through their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
94
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 47 publications
9
94
0
1
Order By: Relevance
“…As with cocaine and other abused drugs, a single injection of morphine was found to increase the ratio of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)toN-methyl-D-asparticacid(NMDA) excitatory postsynaptic currents (EPSCs) 24 hours after administration, consistent with long-term potentiation (LTP) of glutamatergic synapses onto DA neurons (Saal et al 2003). Recently, it has also been reported that acute morphine induces AMPAR receptor (AMPAR) redistribution in VTA in a manner similar to cocaine, specifically an insertion of GluA2-lacking AMPARs (Brown et al 2010). Brown et al observed an increased rectification index and increased cytoplasmic GluA2 AMPAR in response to acute morphine, an effect that is recapitulated by direct stimulation of DA neurons in VTA using selective channelrhodposin 2 expression (Brown et al 2010), directly implicating DA activity/signaling within VTA to glutamatergic regulation.…”
Section: Acute Opiate-induced Synaptic Plasticitymentioning
confidence: 80%
“…As with cocaine and other abused drugs, a single injection of morphine was found to increase the ratio of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)toN-methyl-D-asparticacid(NMDA) excitatory postsynaptic currents (EPSCs) 24 hours after administration, consistent with long-term potentiation (LTP) of glutamatergic synapses onto DA neurons (Saal et al 2003). Recently, it has also been reported that acute morphine induces AMPAR receptor (AMPAR) redistribution in VTA in a manner similar to cocaine, specifically an insertion of GluA2-lacking AMPARs (Brown et al 2010). Brown et al observed an increased rectification index and increased cytoplasmic GluA2 AMPAR in response to acute morphine, an effect that is recapitulated by direct stimulation of DA neurons in VTA using selective channelrhodposin 2 expression (Brown et al 2010), directly implicating DA activity/signaling within VTA to glutamatergic regulation.…”
Section: Acute Opiate-induced Synaptic Plasticitymentioning
confidence: 80%
“…This implies a potential role of DA signaling in triggering cocaine-evoked adaptations in the LHb (Kowski et al, 2009;Shen et al, 2012). In the VTA, cocaine triggers synaptic plasticity via its action on the DA transporter (Brown et al, 2010a). Therefore, cocaine may lead to a surge in DA in LHb, which may account for the cellular mechanism triggering the synaptic potentiation onto LHb neurons.…”
mentioning
confidence: 99%
“…For example, SERT knockout mice exhibit greater rewarding effects of cocaine in the conditioned place preference paradigm compared with wildtype mice (Sora et al, 2001). More sophisticated genetic models with a triple amino acid mutation in the DAT gene showed that DAT inhibition is necessary for cocaine-induced conditioned place preference (O'Neill et al, 2014) and cocaine-evoked synaptic plasticity (Brown et al, 2010). Clinical studies that assess pharmacological interactions between a psychostimulant and receptor-selective antagonists or well-characterized transporter ligands shed light on specific molecular target mediating subjective effects and acute toxicity in humans.…”
Section: Methods For Studying Transporter and Receptor Pharmacology Imentioning
confidence: 99%